Accumulation of Macromolecular Particles in the Reticuloendothelial System (RES) Mediated by Platelet Aggregation and Disaggregation - van Aken, W.G; Vreeken, J (Thrombosis and Haemostasis, 1969)
Carbon particles cause platelet aggregation in vitro and in vivo. Prior studies established that substances which modify thrombocyte aggregation also influence the rate at which carbon is cleared from the blood.This study was performed in order to elucidate the mechanism by which the carbon-platelet aggregates specifically accumulate in the RES.Activation of fibrinolysis by urokinase or streptokinase reduced the carbon clearance rate, probably due to generated fibrinogen degradation products (FDP). Isolated FDP decreased the carbon clearance and caused disaggregation of platelets and particles in vitro. Inhibition of fibrinolysis by epsilon-amino-caproic acid (EACA), initially accelerated the disappearance of carbon and caused particle accumulation outside the RES, predominantly in the lungs. It is supposed that platelet aggregation and locally activated fibrinolysis act together in the clearance of particles. In the normal situation the RES with its well known low fibrinolytic activity, becomes the receptor of the particles.